2008
DOI: 10.3171/jns/2008/108/4/0642
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care and outcomes among elderly individuals with primary malignant astrocytoma

Abstract: Object This study was undertaken to evaluate the association between age at diagnosis, patterns of care, and outcome among elderly individuals with anaplastic astrocytoma (AA) and glioblastoma multiforme (GBM). Methods Using the Surveillance, Epidemiology and End Results database, the authors identified 1753 individuals with primary GBM and 205 individuals with primary AA (diagnosed between June 1991 and December 1999) who were 66 years and older and whose records were linked to Medicare information. To facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 36 publications
(9 reference statements)
4
70
0
2
Order By: Relevance
“…Recent large population-based cohorts of patients with GB demonstrated a marked decrease in median survival with increasing decade of age, and in particular showed a median survival of approximately 6 months in patients age 65 and older. [4][5][6]14 With an aging population and improved diagnostic tools the incidence of GBM has been steadily increasing over the last 20-30 years, and this increase is almost exclusively observed in patients older than 70 years. 15 Median age at diagnosis for GB was 64 years over the years 2002-2006 from a large United States (US)-based cancer registry.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent large population-based cohorts of patients with GB demonstrated a marked decrease in median survival with increasing decade of age, and in particular showed a median survival of approximately 6 months in patients age 65 and older. [4][5][6]14 With an aging population and improved diagnostic tools the incidence of GBM has been steadily increasing over the last 20-30 years, and this increase is almost exclusively observed in patients older than 70 years. 15 Median age at diagnosis for GB was 64 years over the years 2002-2006 from a large United States (US)-based cancer registry.…”
Section: Epidemiologymentioning
confidence: 99%
“…6 Similar results were reported from three other population-based reviews and are in part felt to be related to the general poorer condition of older patients with newly diagnosed GB as well as an increasing incidence of comorbidities in this older cohort. 1,5,6,14 In a review by Kita and colleagues, best supportive care only was increasingly the treatment given to older patients: in those aged 55-64, 65-74, and 75 years it was given in 27%, 44%, and 75% of patients, respectively. 5 In addition, the report on the Ontario experience documented that the proportion of patients spending 100% of their survival time in hospital in the age groups 60-69, 70-79, and 80 increased from 21.9%, to 38%, and 49.5%, respectively, so that clearly the quality of survival decreases with increasing age in a population-based review.…”
Section: Patterns Of Carementioning
confidence: 99%
“…It has been demonstrated that gross total resection has a survival advantage compared with partial resection and certainly compared with biopsy alone. 2,3 Few studies have explored the association between age and short-term postoperative outcomes, and the reports have been conflicting. [19][20][21][22] By using samples from patients who underwent resection of both primary and metastatic tumors, 2 studies associated age with an increased risk of major complications.…”
Section: Interpretations In the Context Of The Literaturementioning
confidence: 99%
“…Fourth, we did not have data on the size, exact location, number, or type of primary lesions for patients who had metastasis (n ¼ 380); whether patients received whole-brain radiotherapy before resection; or the extent of resection, all of which have been previously identified as affecting survival. [2][3][4][5] However, postoperative complications and short-term mortality reportedly were similar between patients who underwent craniotomy for a single tumor resection versus multiple tumor resections 4 and, although it has been observed that the type of primary lesion affects overall survival, 25 no study to date has demonstrated a difference in postoperative short-term outcomes. Fifth, because there are suboptimal data on preoperative and postoperative neurologic function, these results cannot be compared against studies that only assessed neurologic function as a postoperative complication.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation